How to Human : An Incomplete Manual for Living in a Messed-Up World - Connor, Alice (Book collections on Project MUSE., 2019)
Being human is hard. Being a good human is even harder. Practicing kindness, honesty, and self-awareness in the face of doubt, failure, ambiguity, and vulnerability can feel insurmountable. How to Human is here to help. Alice Connor draws on nearly a decade of experience as a college chaplain to provide a tender and irreverent take on one of life's most fundamental questions: how to be a better human in a world dead set against it. Connor offers sage wisdom and no-nonsense realism through real-life examples that strike right at the rashes and rubs of the human experience. She'll take you by the hand, tell you what you need to hear, and encourage you to embrace the chaos. How to Human will help you see life as an experiment--not a quest for the right answers.